Determinants and Aspirants of Nurse Migration from Nepal: A Cross Sectional Study from Kathmandu - Munikar, Sabika; Thapa, Kanchan (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Migration is the result of interplay of many factors, which guide the individual’s decision to emigrate. Health workers tend to go where the working conditions are best. This study aims to identify the determinants and aspirants of nurse migration from Nepal.Methods: A descriptive cross sectional study was conducted using interview technique. A semi structured questionnaire was administered to all nurses working at a private hospital who met the inclusion criteria.Results: Majority of the participants were 20- 30 years old (93.20%), Hindu (86.5%), Chhetri (35.1%), unmarried (66.2%), had completed intermediate level (58.1%). Among the total respondents, 93.20% intended to migrate to abroad and more than half of the respondent (62.20%) preferred Australia as destination. The general factor provoking migration was bad nature of politician (98.6%) followed by political instability (90.5%) and non-availability of job (90.5%). The major working condition and social factors provoking migration were occupational security in other country (85.10%) and peer influence (91.9%) respectively. The reasons for migration as mentioned by respondents were education (59.50%) followed by better job opportunities (40.50%), better living standard (21.60%) and family and/or peer pressure (8.10%).Conclusions: The present study concluded that majority wanted to migrate and Australia was famous choices for nurses. Bad nature of politician, occupational security in other country and peer influence were factors for migration.  The major purpose for migration was education.